74 Non-invasive Assessment of Pulmonary Haemodynamics in Fontan Patients. (3rd June 2016) - Abiodun, Aderonke; Pickup, Luke; Moore, Heather; Bowater, Sarah; Thorne, Sara; Hudsmith, Lucy; Clift, Paul
Abstract : Introduction: The Fontan circulation relies on a low pulmonary vascular resistance. At present the gold standard method of measuring this is with invasive cardiac catheterisation which can be difficult in this group. Previous work has shown that pulmonary vascular resistance is inversely correlated with pulmonary capacitance which can be approximated non-invasively using data derived from a maximal cardiopulmonary exercise test (CPEX). We have determined the non-invasive pulmonary artery capacitance (Ventilatory Product) in a large cohort of adult Fontan patients. Methods: 220 patients under regular follow up at University Hospital Birmingham were identified and CPEX results were available for 131 patients. We subdivided these into two groups, those with an atriopulmonary Fontan (AP) and combined those with lateral tunnel and total cavo-pulmonary connexion (TCPC). Parameters obtained were: NYHA functional class, maximum workload, ventilatory product, peak oxygen consumption, peak end tidal CO2 and VE/VCO2 slope. Results: 77 patients with TCPC/lateral tunnel versus 54 AP Fontan were included. In the AP Fontan group, mean ventilatory product correlated positively with pVO2 (r 2 =0.344) and maximum workload (r 2 =0.515) and negatively with VE/VCO2 slope (r 2 =-–0.366). In the combined TCPC/lateral tunnel Fontan group, mean ventilatory product correlated positively with pV02 (r 2 =0.484) and maximum workload (r 2 =0.485) and negatively with VE/VCO2 slope (r 2 =-0.127). When determined for each functional class ventilatory product was as follows in TCPC/lateral tunnel group: NYHA I 355.8 +/-±100, NYHA II 272.14  ±   105, NYHA III 241.76 ± 90.3. In the AP Fontan group mean ventilatory product was as follows: NYHA I 349.2 ±  131.8, NYHA II 271.5  121.5, NYHA III 273.9 +/- 140.6. The mean VO2 peak was significantly higher in the combined TCPC/lateral tunnel group (26.64 vs 20.56, p = 0.00). Further sub analysis within each functional class between both groups also showed statistical significance. TCPC/lateral NYHA class I mean V02 peak 29.56 vs 25.11 vs (p = 0.01), class II mean V02 peak 22.72 vs 18 (p = 0.038) and class III mean 22.14 vs 15.31 (p = 0.018). Discussion: Invasive measurements of PVR are difficult in the Fontan patient. We have demonstrated that a non-invasive indirect measurement of pulmonary artery capacitance -the ventilatory product, correlates with measures of performance, and negatively correlates with VE/VCO2, which is known to be of prognostic significance in heart failure. Furthermore our data shows that ventilatory product falls with increasing functional class. From this, we propose that the ventilatory  product may be used to identify Fontan patients suitable for pulmonary vasodilator therapy. Our hypothesis however will require testing in prospective studies of pulmonary vasodilator therapy in Fontan patients.